Community pharmacy personal's perception, attitude and dispensing practice towards antibiotics in selected districts of Terai region of province 1, Eastern Nepal. - Goswami,Nikita (2020)
ABSTRACT: Background: In the developing countries like Nepal, people depend more on community pharmacies to obtain medications due to quick access and easy availability. Many studies showed that the irrational dispensing of antibiotics by the drug dispensers adds to antimicrobial resistance. Objective: The aim of our study is to assess the perception, attitude and dispensing practice of retail community pharmacy drug dispensers in the three districts of Province-1, Nepal, and to identify the contribution of drug dispenser's, attitude and practice of antibiotics in irrational dispensing of antibiotics. Method: A descriptive, cross sectional and self-administered questionnaire based survey was conducted in 312 pharmacies of Jhapa, Morang and Sunsari districts of Eastern Nepal. The data were collected from the drug dispensers working in these retail community pharmacies. The study was conducted for six months between March to august 2019. Result: Out of 312 drug dispenser, Majority of the drug dispensers (39.1%) were assistant pharmacists followed by other paramedical professionals (32%), pharmacy oriented registered professional 19.6%, whereas only 4.2% were Pharmacist. 76.9% of the drug dispensers agree that there is problem in dispensing antibiotics without prescription. 86.9% of the drug dispensers are aware of this provision that dispensing antibiotics without prescription is not legal but still nearly one third (34.9%) of the drug dispensers in the study area admit that they dispense antibiotics without prescription. 32.7% of the drug dispensers were not aware that the misuse of the antibiotics leads to the loss of sensitivity of to specific pathogens and 34.3% of the drug dispensers think that antibiotics are given to reduce any kind of pain and inflammation. However, 94.5% of the dispensers at the community pharmacy suggest patients to follow drug dosage regimen adherence and course completion but only 34.6% of them take follow-up feedback after dispensing antibiotics. Conclusion: Antibiotics dispensing without prescriptions by non-pharmacists was seen. Perception of drug dispenser was associated with inappropriate dispensing of antibiotics. These practice and attitude may add to the existing burden of antibiotics resistance in worldwide. There is need of strict regulation and monitoring of the concerned authority for the dispensing of antibiotics. Provision of training to Upgrade Drug dispenser's knowledge should be made also the drug dispensers need to understand their role in appropriate use of antibiotics. Keywords: Community pharmacy, Pharmacist, Drug dispensers, antibiotics resistance, irrational drug dispensing.